Bisnis Dan Marketing Mix Home Industry Jamu Tradisional Sinoman Di Kota Palangka Raya - Sofyan Hakim; Muhammad Riza Hafizi; Hasnita Hasnita; Haidi Hajar Widagdo (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Business activity is an activity that requires very serious thinking and understanding to improve marketing. A product is created that is a superior product and has quality, because the business world competition is always there. If the product created does not have an advantage, then the product created will not excel in the market. If a business experiences a decline in sales, then the business must try to take steps or ways to improve to save the business being run. The activities carried out in this PKM are to find out the Marketing Mix strategy of Sinoman traditional herbal medicine in the city of Palangka Raya, by implementing marketing with a form of Marketing Mix strategy that can support marketing products with the 4P Method. This paper aims to build community service activities in an effort to knowledge and business development of Home Industry in the city of Palangka Raya. This activity can be taken benefit and wisdom, and the findings of this service lie in a strategy that should be applied in business is Marketing Mix, about the steps to apply the 4Ps consisting of Product, Price, Distribution/Place and Promotion. The first part of the main step must be done by business people is to plan product marketing strategies, so that the goal in doing business to obtain profit can be achieved maximally.